Råttors sjukdomar - Englund, Anna (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
This examination paper is about diseases of rats. The examination paper also includes sampling techniques, administration techniques and radiography. A detailed account of diseases of rats and their symptoms has been included. This examination paper is primarily written for veterinary technicians but also for others with interest in the subject.